PENERAPAN SISTEM PENGONTROL ALAT ELEKTRONIK BERBASIS INTERNET OF THINGS PADA PROGRAM STUDI INFORMATIKA UNIVERSITAS SULAWESI BARAT - Ahmad Muaz Asiz; Asmawati S; Musyrifah Musyrifah (Universitas Nusa Cendana, 2022)
The use of electrical energy, especially in the informatics study program room, is very important because negligence is often found in the use of electrical energy in the informatics study program room. The informatics study program room was the target of research because the location was equipped with electronic fans, lights and wi-fi networks, the head of the informatics study program suggested making a remote control so that it strengthened the background of this research. The purpose of this study is to implement a remote-control system for electronic devices, using nodeMCU and relay as a web server to control the switch online. As well as applying the waterfall method in the design to implementation process, system testing is carried out using the black box method to find out the system is working as expected. From the results of field testing, it was found that the implementation of NodeMCU and relay as a web server to control the switch online makes it easier to control electronic equipment remotely if there is a good internet network.